Evolution of HER2-low expression from primary to paired metastatic gastric cancer lesions - Wen-Zhuo He; Yuan-Zhong Yang; Chen-Xi Yin; Xin-Yi Xian; Jia-Mei Gu; Jia-Hong Yi; Ju Xue; Yue Zhao; Fang Wang; Wan-Ming Hu; Liang-Ping Xia (npj Precision Oncology)
Abstract HER2-low expression has recently gained considerable attention as an actionable biomarker in gastric cancer. However, changes in HER2-low expression between primary and metastatic gastric cancers remain inadequately explored. This study included consecutive patients diagnosed with metastatic gastric cancer with both primary and metastatic tumors, between January 2014 and December 2023. HER2 status was evaluated in both primary and matched metastatic tumors. A total of 332 patients were enrolled, with HER2-negative, HER2-low, and HER2-positive statuses were observed in 226, 81, and 25 primary tumors, respectively, and in 175, 104, and 53 metastatic tumors, respectively. Among the 226 patients with HER2-negative primary tumors, 74 and 23 developed HER2-low and HER2-positive metastatic tumors, respectively. Conversion from HER2-negative primary to HER2-low metastatic gastric cancer was associated with metachronous and non-peritoneal metastasis. Overall, re-biopsy to evaluate HER2 status may be necessary, potentially broadening the patient population eligible for targeted HER2 therapy.